2022
DOI: 10.1027/2157-3891/a000060
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and School Context Differentiate Nigerian Adolescents’ Profiles of Substance Use

Abstract: Abstract. Substance use among Nigerian adolescents has increased significantly in the past decade, highlighting the need to implement evidence-based, effective prevention programs as one strategy to help reverse this trend. This study aimed to identify profiles of adolescent substance use and parenting and school correlates of these profiles to inform preventive interventions. Latent class analysis identified four distinct use patterns in 2,004 adolescents (46% male; M = 14.8 years) attending public and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Reports from Nigeria indicate on‐going concerns regarding adolescents' use of alcohol and other drugs, including misuse of over‐the‐counter (OTC) and prescription medications (Agwogie et al, 2022; Mehanovic et al, 2020; Obadeji et al, 2020; Vigna‐Taglianti et al, 2019). For example, non‐medical use of codeine and tramadol has been on the rise among adolescents and young adults in Nigeria (Mehanovic et al, 2020; Vigna‐Taglianti et al, 2019).…”
Section: Sex Differences In the Role Of Protective Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports from Nigeria indicate on‐going concerns regarding adolescents' use of alcohol and other drugs, including misuse of over‐the‐counter (OTC) and prescription medications (Agwogie et al, 2022; Mehanovic et al, 2020; Obadeji et al, 2020; Vigna‐Taglianti et al, 2019). For example, non‐medical use of codeine and tramadol has been on the rise among adolescents and young adults in Nigeria (Mehanovic et al, 2020; Vigna‐Taglianti et al, 2019).…”
Section: Sex Differences In the Role Of Protective Factorsmentioning
confidence: 99%
“…Many studies of parental and family influences on adolescent substance use in Nigeria have focused on risk factors such as parental substance use (Mehanovic et al, 2020; Obadeji et al, 2020; Ogunsola & Fatusi, 2017) or permissive attitudes towards substance use (Mehanovic et al, 2020; Ogunsola & Fatusi, 2017). Fewer studies have highlighted the important role that protective factors in the family domain play in predicting adolescent substance use and misuse (Agwogie et al, 2022; Ogunsola & Fatusi, 2017). For example, Ogunsola and Fatusi found that among urban students from Osun state, parental disapproval of substance use was associated with a lower likelihood of adolescent substance use; among rural students, connection to parents was associated with less substance use.…”
Section: Sex Differences In the Role Of Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles included in this issue exemplify this. In addition to Mylonas et al’s (2023) Greek adaptation of the Situational Triggers of Aggressive Responses scale, they showcase work conducted with adolescents and young adults on three continents, Africa (Nigeria; Agwogie et al, 2023), Europe (Switzerland; Bachem et al, 2023) and Asia (Georgia; Bachem et al, 2023). The differences they present highlight the extent to which context matters.…”
mentioning
confidence: 99%
“…Yet, today, this view has become contested even in the natural sciences as evident in, for example, the socio-medical model in medicine (e.g., Hogan, 2019) and quantum physics (e.g., Fingelkurts et al, 2019). Deliberately considering the role of context in psychology might allow us to identify nuances that “matter” and which might present intervention points, for example, in relation to stress, mental health, and substance abuse among young people, which are the variables considered in the work by Bachem et al (2023) and Agwogie et al (2023) in this IPP issue, while also showing commonalities despite varying contexts. This issue concludes with two special section articles.…”
mentioning
confidence: 99%